Design of Hyacinth Dressings as an Alternative to Sterile Wound Covers in Diabetes Mellitus Wounds - Desyta Dwiyana Aviyanti; Tri Cahyo Sepdianto; Agus Khoirul Anam (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Diabetic Wounds are a complication of diabetes that requires optimal care in a hospital and can cause serious complications and require significant costs. The method used in this study is Research and Development, the research procedure uses the ADDIE model which consists of 5 stages including Analysis, Design, Development, Implementation. The number of participants was 14 people consisting of 2 diabetic wound patients, 10 nurses from the Mitra Medika Clinic, 2 expert validators, namely doctors from the Mitra Medika Clinic and a supervisor of a diploma three Nursing lecturer in Blitar. Based on the results of the research conducted in stages, in the final stage the expert validator assessor stated that the product was suitable for use with a criterion value of 81%-100%. So that the product resulting from this study can be an Alternative Sterile Wound Cover for Diabetic Wounds so as to accelerate wound healing that is easily available, affordable and environmentally friendly.